3t-t=-22

Simple and best practice solution for 3t-t=-22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3t-t=-22 equation:


Simplifying
3t + -1t = -22

Combine like terms: 3t + -1t = 2t
2t = -22

Solving
2t = -22

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Divide each side by '2'.
t = -11

Simplifying
t = -11

See similar equations:

| 458=6x+308 | | -8(-2x-5)-4x=88 | | -34=-4(x+4)-5x | | y=(8-6k)x | | 3y-9x=21 | | 3a=2*12 | | 9(x+8)+6=4(x+7) | | -3x+4+3x-3=5 | | 1.09=1.3h | | 9c=7*54 | | 6x-2+7x=180 | | 5x-8+3x=24 | | (2x+7)(x+5)= | | 8=4x+4-3x | | 8(z-6)=-16 | | 2212=-14c | | 14d=126*3 | | -8(4v+5)=-104 | | 3[4y+2(x-3)+2y-4]= | | -2(y-5)= | | -4(2x-2)=22 | | 456=6x+308 | | 12x+5y+7= | | 5x-10=8x+6 | | 4ax=6 | | 23p=529 | | 1/5(5x+20)4/1-5= | | 5-(-8)-40+(-2)= | | 3x-31-x+6= | | 6x-(3x+7)=4x-10 | | 5=(-2x)+3x | | -3y=471 |

Equations solver categories